2015
DOI: 10.1051/limn/2015016
|View full text |Cite
|
Sign up to set email alerts
|

Short-term responses of glass eels transported from UK to small Belgian streams

Abstract: -Restocking of inland waters with glass eels is one of the recovery options to prevent the decline of European eel Anguilla anguilla (L.) populations. We studied the growth, dispersion, density and habitat preferences in the imported glass eels from UK and stocked in three typologically different small Belgian streams, using electrofishing surveys around the single release point, 1 year following stocking. Our results clearly support that the recaptured individuals stocked in our streams farther from the sea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 35 publications
(39 reference statements)
2
47
1
Order By: Relevance
“…Particularly in the River Meuse, the upstream habitats are no longer colonized by eels and will therefore be emptied of this fish species when the last resident eels migrate to spawn. In this context, eel conservation actions such as well-targeted glass eel stocking to enhance yellow eel abundance may be necessary conservation measures, if adequately carried out (Ovidio et al 2015;Brämick et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the River Meuse, the upstream habitats are no longer colonized by eels and will therefore be emptied of this fish species when the last resident eels migrate to spawn. In this context, eel conservation actions such as well-targeted glass eel stocking to enhance yellow eel abundance may be necessary conservation measures, if adequately carried out (Ovidio et al 2015;Brämick et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The Mosbeux River is a typical trout zone, and the Vesdre River is a barbel zone (Huet, ). This study site was selected because it was subjected to the restocking of glass eels ( n = 4155) in 2013, which were released at a single point in the Mosbeux River, 0.040 km upstream of its mouth (Ovidio et al, ). During the study period (from 2014 to 2017), the observed mean width and depth of the Mosbeux River were 2.40 and 0.18 m, respectively, compared with 14.90 and 0.44 m, respectively, for the Vesdre River.…”
Section: Methodsmentioning
confidence: 99%
“…Electrofishing (EFKO, 3.0 kVA) using hand nets with a 40 × 40 cm diameter and 2 × 2 mm mesh was used to capture the small restocked eels, following the technique used by Ovidio et al (). From November 2014 to September 2016, nine electrofishing sessions (S 1 –S 9 ) were performed (Table ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations